Causes of oyster larvae mortality in south Puget Sound - Cardwell, Rick D; United States. National Oceanic and Atmospheric Administration; Marine EcoSystems Analysis Program (Boulder, Colo. : Marine Ecosystems Analysis Program [Office], Environmental Research Laboratories, 1979)
Chiefly tables Bibliography: p. 26-29 Mode of access: Internet.